Design of polymeric binders to improve the properties of magnesium phosphate cement. (5th July 2021) - Zárybnická, Lucie; Machotová, Jana; Mácová, Petra; Machová, Dita; Viani, Alberto
Highlights: Designed eco-friendly polymer emulsions improved the properties of Magnesium cements. Self-crosslinking is beneficial and exhibits synergistic effect with cement reaction. More crystals, lower porosity, higher toughness, lower reaction rates, were obtained. Abstract: In the context of reducing the environmental impact of cement manufacturing, magnesium phosphate cements raise interest as alternative binders in construction, for immobilization of wastes, and recycling purposes. Their use in applications is somehow limited by short setting time, brittleness and low water resistance; this calls for the use of additives. Two polymer additives were designed adopting emulsion polymerization, an environmentally friendly solution to make available polymers as water-based latex dispersions. The composites containing 5 wt% of polymer, exhibited better elastic behaviour, with up to twice the toughness of the reference sample and of a sample produced with commercial styrene-butadiene rubber latex. Moreover, the additives reduced the apparent porosity, promoted phosphate crystallization, modified the size and shape of crystals, and effectively retarded the reaction, extending working time. The acrylic emulsion developing keto-hydrazide self-crosslinking reaction imparted better properties to the composite, thanks to the synergistic effect with the MPC setting reaction.